The sustainable business blueprint : planning, performance, risk, reporting, and assurance - Rezaee, Zabihollah, 1953- (Routledge, 2025)
"Understanding how to build and manage a sustainability business plan has become a business imperative as investors demand, regulators require, and customers increasingly expect companies to report their financial economic sustainability performance (ESP) and non-financial environmental, social, and governance (ESG) sustainability information. This book provides both the rationale and key practical steps in how to approach business sustainability planning, performance, risk, reporting, and assurance. This comprehensive book covers all the areas that a business would need to embed, articulate, and execute a strategy of profit-with-purpose in promoting shared value creation for all stakeholders. It addresses drivers, sources, and international guidelines (GRI, IIRC, SASB, FASB, PCAOB, IAASB, ISSB) in promoting business sustainability factors, and the link between ESG performance and financial performance. It presents key performance indicators (KPIs) of ESP and ESG dimensions of sustainability performance. It also provides templates for performance, risk, and disclosure presents cases and examples of why to disclose ESG performance, what to disclose, where and how to disclose ESG performance information. For businesses wanting a detailed understanding of how to deliver on these important areas, including boards of directors, senior management, financial officers, internal auditors, external auditors, legal counsel, investors, and regulators, this book is an invaluable resource"-- Provided by publisher.
Keywords: Management -- Environmental aspects.; Sustainable development -- Management.; Business planning -- Environmental aspects.; Environmental reporting.; elektronické knihy; electronic books